2016
DOI: 10.1093/jnen/nlw004
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Abnormalities of the Neuromuscular Junction in the Trembler-J Homozygote Mouse Model of Congenital Hypomyelinating Neuropathy

Abstract: Mutations in peripheral myelin protein 22 (PMP22) result in the most common form of Charcot-Marie-Tooth (CMT) disease, CMT1A. This hereditary form of peripheral neuropathy is characterized by dysmyelination of peripheral nerves, reduced nerve conduction velocity and muscle weakness. A PMP22 point mutation in leucine 16 to proline (L16P) underlies a form of human CMT1A as well as the Trembler-J mouse model of CMT1A. Homozygote Trembler-J mice (TrJ) die early postnatally, fail to make peripheral myelin, and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Whole diaphragm muscles were dissected and pinned on a Sylgard-coated dish containing oxygenated Krebs-Ringer's solution at RT as described (Scurry et al, 2016). After 30 min of perfusion, the left phrenic nerve was drawn into a suction electrode and stimulated with supra-maximal square waves from an SD9 stimulator (2–5 V, 0.1 ms for adults; 4–10 V, 0.1 ms for embryos) or from an S48 stimulator coupled to a SIU5 stimulus isolation unit (both from Grass, Quincy, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole diaphragm muscles were dissected and pinned on a Sylgard-coated dish containing oxygenated Krebs-Ringer's solution at RT as described (Scurry et al, 2016). After 30 min of perfusion, the left phrenic nerve was drawn into a suction electrode and stimulated with supra-maximal square waves from an SD9 stimulator (2–5 V, 0.1 ms for adults; 4–10 V, 0.1 ms for embryos) or from an S48 stimulator coupled to a SIU5 stimulus isolation unit (both from Grass, Quincy, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, deterioration of synaptic transmission occurs in advance of denervation and axon degeneration in neurodegenerative diseases such as spinal motor atrophy (SMA; Martinez et al, 2012) and amyotrophic lateral sclerosis (ALS; Shahidullah et al, 2013). Impaired neurotransmission also is a feature of muscular dystrophy (MD; van der Pijl et al, 2016) and inherited peripheral neuropathies such as Charcot-Marie Tooth disease Types 1 and 2 (CMT1, 2; Yin et al, 2004; Spaulding et al, 2016) Recently, we observed functional defects in the absence of denervation in an animal model of congenital hypomyelinating neuropathy (CHN; Scurry et al, 2016). Other forms of peripheral neuropathy such as type 2 diabetes also exhibit defective neuromuscular transmission (Allen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…10,31 Along with the nerve defects, distinct morphological changes at the neuromuscular junction (NMJ) have been observed in samples from 2-month-old heterozygous TrJ mice, whereas a study of homozygous animals detected structural and functional deficits at the NMJ with development. 5,32 Although neither of these studies examined the TA muscle, significant changes in muscle fiber phenotype were detected in the EDL at 2 months of age. 5 Here we focused on the TA to determine the impact of neuropathic disease on neuromuscular function and skeletal muscle morphology.…”
Section: Discussionmentioning
confidence: 96%
“…In rodent models of CMT1A as well as CMT1E, one can detect early abnormalities in the differentiation and myelination of Schwann cells, which then progress to pronounced myelin defects with age . Along with the nerve defects, distinct morphological changes at the neuromuscular junction (NMJ) have been observed in samples from 2‐month‐old heterozygous TrJ mice, whereas a study of homozygous animals detected structural and functional deficits at the NMJ with development . Although neither of these studies examined the TA muscle, significant changes in muscle fiber phenotype were detected in the EDL at 2 months of age .…”
Section: Discussionmentioning
confidence: 99%
“…Such effects raise multiple health concerns as synapse formation is complex and incompletely understood. Exploration of synaptogenesis, particularly the influence of genes products and epigenetic factors on synapse maturation, will increase our understanding of the pathogenesis of conditions in which, "morphology" appears normal, but function is abnormal [152]. Pre and postnatal exposures to environmental factors predispose to the onset of neurodegenerative diseases later in life.…”
Section: Neuropsychiatric Impact Of Pollutionmentioning
confidence: 99%